The Effect of Giving Pork Oil and Egg Yolk as Components of a High Fat Diet on The Hematological and Cholesterol Profiles of Mice (Mus musculus) - Larasati, Anissa Dhea; Allailah, Rashya Jasmine; Syachfitri, Dea Dwyna; Safania, Mocca Cintaura Radya; Rachmania, Revira Yunita; Wardhana, Dewa Drio Putra; Gustiko, Aliyya Lintang; Faruq, Abdullah Umar Al (Journal of Basic Medical Veterinary, 2024)
Background: This study examined the role of a high-fat diet, especially one containing animal fat, in its influence on the hematology of the organism, with mice as research subjects. Hematology, as the study of blood components, is the focus for analyzing the impact of a high-fat diet, which includes animal fats such as lard and egg yolks. Although fats are essential for cell function and nutrient absorption, excessive intake can increase the risk of serious health problems. Purpose: To fill the gap in knowledge by evaluating the effect of lard and egg yolk on the hematological profile of mice. Methods: True Experimental with a Pretest-Posttest Control Group design. The sampling technique used is Simple Random Sampling. The parameters yolk). The sampling technique used is Simple Random Sampling. The parameters observed include blood hematological profiles (Erythrocyte Count, Hemoglobin, and Erythrocyte Index) and cholesterol levels. Results: Expected to provide in-depth insight into the impact of high-fat diets on blood health, provide important contributions to understanding the human health implications, and support the development of more effective nutritional guidelines for managing diet and preventing metabolism-related diseases. Conclusion: It can be concluded that giving pork oil with added egg yolk can increase erythrocyte levels, hemoglobin profile, erythrocyte index (MCV and MCH), and cholesterol levels.